The Relationship Between Gadget Exposure and Musculoskeletal Complaints among Office Workers - Rizky Ananda; Li Wei; M Zainul Hafizi (Media of Health Research, 2025)
Excessive gadget use has become a significant occupational health concern, particularly among office workers who spend extended hours using computers, smartphones, and other digital devices. Prolonged exposure often leads to poor posture, repetitive movements, and increased risk of musculoskeletal disorders (MSDs). This study aims to investigate the relationship between gadget exposure and musculoskeletal complaints among office workers. A cross-sectional survey was conducted involving 250 office employees in Jakarta, Indonesia, and Beijing, China. Data were collected using a standardized questionnaire that assessed duration of gadget use, ergonomic practices, and musculoskeletal symptoms. The results indicated that office workers who used gadgets for more than 6 hours daily had a significantly higher prevalence of neck pain (62.8%), lower back pain (48.5%), and wrist discomfort (35.4%) compared to those with shorter exposure (p < 0.05). Multivariate analysis confirmed that prolonged gadget use, lack of ergonomic awareness, and absence of rest breaks were independent predictors of musculoskeletal complaints. These findings highlight the urgent need for ergonomic interventions and organizational policies promoting healthy digital habits. This research contributes to occupational health literature by providing cross-cultural evidence of gadget-related musculoskeletal risks and emphasizing preventive workplace strategies.